Price Volatility of Cooking Oil in Jambi Province Across Four Market Levels: A Structural Break Approach - Asifa, Asifa; Azizan, Muhammad; Ma'arif, Samsul (Hasanuddin University, 2025)
Cooking oil is one of the nine essential food commodities in Indonesia, whose availability and demand significantly influence fluctuations in both national and regional food prices. This study examines the development trends of cooking oil, analyzing its price volatility, risk levels, and structural changes (structural breaks) across four market levels in Jambi Province. A descriptivequantitative approach was employed, utilizing trend analysis, the coefficient of variation, and structural break tests based on daily data from the Strategic Food Price Information Center (PIHPS) covering the period from January 1, 2020, to December 27, 2024. Jambi Province was chosen as the study location because it is one of the main producers of crude palm oil (CPO)— the primary raw material for cooking oil—yet it continues to experience price volatility and periodic shortages of cooking oil. The results indicate that cooking oil prices fluctuated during the study period, with an overall upward trend. The coefficient of variation at the producer level was relatively higher compared to wholesalers, modern retailers, and traditional markets. Risk analysis further revealed that producers face higher price fluctuations, as they tend to act as price takers, with prices largely determined by market conditions and government interventions. Moreover, a structural break was observed at the wholesale market level on May 10, 2024. These findings highlight the critical role of government intervention in maintaining the stability of national cooking oil prices.